DEET degradation in UV/monochloramine process: Kinetics, degradation pathway, toxicity and energy consumption analysis. (September 2020) - Zhu, Tianxin; Deng, Jing; Xu, Mengyuan; Cai, Anhong; Ye, Cheng; Li, Jun; Li, Xueyan; Li, Qiongsong
Abstract: The degradation of N, N -diethyl- meta -toluamide (DEET) in aqueous solution by the UV/monochloramine (UV/NH2 Cl) process was examined systematically in this study. DEET was resistant to UV photolysis and chloramination, while the synchronous combination of UV irradiation and NH2 Cl can effectively eliminate DEET, which was caused by the generation of hydroxyl radicals and reactive chlorine species. The former played the critical role in DEET degradation, while the contribution of the latter can be ignored. Under all investigated experimental conditions, DEET degradation in the UV/NH2 Cl process followed the pseudo-first-order kinetic model. The water quality parameters exerted the complicated impact. Reducing solution pH and raising water temperature both favored the DEET removal. The presence of sulfate, humic acid and fulvic acid accelerated the degradation, while the introduction of bicarbonate and high-concentration chloride retarded the removal. The plausible degradation pathways of DEET in the UV/NH2 Cl process were proposed through the combination of QTOF/MS analysis and DFT calculation, and mainly involved in the cleavage of C–N bond, dealkylation, mono- and polyhydroxylation. The acute toxicity of reacted solution underwent a trend of first increasing and then decreasing with the prolonged irradiation time, which can be well illustrated by quantitative structure-activity relationship analysis. Electrical energy per order was employed to determine the energy consumption and the optimal conditions were determined as UV fluence of 369.9–493.2 mJ cm −2 and NH2 Cl dosage of 5–20 mg L −1 . Highlights: The synchronous combination of UV irradiation and NH2 Cl significantly facilitated DEET degradation. In the UV/NH2 Cl process, water quality parameters exerted completely different effects. HO· acted as dominant radical on DEET degradation by the UV/NH2 Cl process in pH range of 6.0–8.0. The DEET degradation pathway in the UV/NH2 Cl was elaborated in detail. Electricity consumption was the major contributor to the overall consumption.